Enhanced Retinal Ganglion Cell Survival in Glaucoma by Hypoxic Postconditioning After Disease Onset - Gidday, Jeffrey M. (Neurotherapeutics, 2014)
The neuroprotective efficacy of adaptive epigenetics, wherein beneficial gene expression changes are induced by nonharmful “conditioning” stimuli, is now well established in several acute, preclinical central nervous system injury models. Recently, in a mouse model of glaucoma, we demonstrated retinal ganglion cell (RGC) protection by repetitively “preconditioning” with hypoxia prior to disease onset, indicating an epigenetic approach may also yield benefits in chronic neurodegenerative disease. Herein, we determined whether presenting the repetitive hypoxic stimulus after disease initiation [repetitive hypoxic “postconditioning” (RH-Post)] could afford similar functional and morphologic protection against glaucomatous RGC injury. Chronic elevations in intraocular pressure (IOP) were induced unilaterally in adult male C57BL/6 mice by episcleral vein ligation. Mice were randomized to an RH-Post [1 h of systemic hypoxia (11 % oxygen) every other day, starting 4 days after IOP elevation] or an untreated control group. After 3 weeks of experimental glaucoma, the 21–27 % reduction and 5–25 % prolongation in flash visual-evoked potential amplitudes and latencies, respectively, and the 30 % impairment in visual acuity were robustly improved in RH-Post–treated mice, as was the 17 % loss in RGC soma number and 20 % reduction in axon integrity. These protective effects were observed without RH-Post affecting IOP. The present findings demonstrate that functional and morphologic protection of RGCs can be realized by stimulating epigenetic responses during the early stages of disease, and thus constitute a new conceptual approach to glaucoma therapeutics. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1007/s13311-014-0330-x) contains supplementary material, which is available to authorized users.